A cartographic approach coupled with optimized sizing and management of an on-grid hybrid PV-solar-battery-group based on the state of the sky: An african case study. (October 2021) - Jedou, Eslemhoum; Ndongo, Mamoudou; Ali, Mohamed Mahmoud; Yetilmezsoy, Kaan; Bilal, Boudy; Ebeya, Cheibany Cheikhe; Kébé, Cheikh Mohamed Fadel; Ndiaye, Papa Alioune; Kıyan, Emel; Bahramian, Majid
Graphical abstract: Highlights: Electricity consumption is mapped using a combined cartographic methodology. State of the sky impact is explored for the first time on energy management strategies. LF strategy provides the best load monitoring by minimizing the generator uptime. Energy management strategies play a pivotal role as hybrid solar system control tools. Abstract: A novel optimized sizing and management strategy of a grid-connected hybrid photovoltaic (PV)-solar-battery-group system were proposed for the electrification of residential consumers in Northwest Africa (a case of Mauritania), and the influence of the state of the sky (clear, moderately overcast, and overcast) was analyzed according to the load flowing (LF) and the cycle charging (CC) strategies. In order to mitigate the pressure on the national grid, consolidate the consumer autonomy, minimize the cost of medium- and long-term consumption bills, and CO2 -related emissions, a cartographic approach was conducted as the first attempt to map the electricity consumption potential for buildings in the city of Nouakchott (Mauritania) using a geo-referenced database. ArcGIS®, HOMER Pro®, and MATLAB® softwares were used for the establishment of the load profile, optimized sizing of the PV-batteries-group-grid system, and calculation of the lightness index, respectively. The LF strategy provided the best monitoring of the load throughout the day by minimizing the generator uptime. The techno-economic analysis revealed the values of cost of energy (COE) and net present cost (NPC) as follows: COE = $0.0549/kWh and NPC = $24, 796 for the LF PV-batteries-grid strategy, COE = 0.0646 $/kWh and NPC = $23, 380 for the CC PV-batteries-grid strategy, and COE = $0.17/kWh and NPC = $23, 262 for the case of the grid on its own.